Effects of inflammation and fibrosis on pulmonary function in diffuse lung fibrosis. Issue 9 (September 1990) - Chinet, T; Jaubert, F; Dusser, D; Danel, C; Chrétien, J; Huchon, G J
Abstract : To investigate the relation between lung function and inflammation and fibrosis in patients with diffuse lung fibrosis, a study was made of untreated patients without appreciable airway obstruction (14 patients with cryptogenic fibrosing alveolitis and seven with pneumoconiosis). Quantitative assessment of inflammatory infiltration and fibrosis was carried out on open lung biopsy specimens and compared with lung volumes, carbon monoxide transfer factor (TLCO), TLCO corrected for alveolar volume (TLCO/VA), and arterial blood gases at rest and during exercise. The degree of fibrosis and the degree of cellular infiltration were positively correlated. Lung volumes and TLCO were correlated with the grades of fibrosis and cellular infiltration of alveoli; arterial blood gases during exercise tended to correlate with both fibrosis and infiltration (p less than 0.06). In contrast, morphological data were not correlated with gas exchange at rest or with TLCO/VA. It is concluded that, in untreated patients with diffuse lung fibrosis, lung volumes, TLCO, and arterial blood gases during exercise reflect the lung lesions, and that the pulmonary function tests used cannot discriminate between fibrosis and infiltration of the lung by inflammatory cells.